Efecto de la aplicación de cuatro tipos de abonos orgánicos en el cultivo de babaco (vasconcella pubescens x estipulata) bajo invernadero en la parroquia Santiago – cantón Loja - Quezada Quezada, Angel Moisés (2014)
The present research on effect of the implementation of four types of organic fertilizers, was carried out in the rural parish of St James, which is located 33 km from the city of Loja, in the floor of 2600 m.s,n.m. in the period from January to September 2010; it was investigated on the effects of organic fertilization of the babaco with four fertilizers produced in the area, which raised the following objectives: Determine the effect of four types of organic fertilizers in the productive performance of babaco under greenhouse in the parish church of Santiago. Disseminate the results. First, they built a greenhouse with the technical standards with a surface area of 24m x16m (384m2), are also carried out the physical analysis, soil chemical and organic fertilizers to know the contents of macro and micro elements; as also developed organic fertilizers: Humus, Bokashi, compost and Fosfoestiercol using materials of the east. In the treatment of the babaco bioassay in the parish Santiago, canton, and province of Loja, with a temperate climate and clay loam soils, practically neutral (pH =6.08 ), high in organic matter (2.63 % ), low in total nitrogen (0.13 % ), low in phosphorus (6.2 ppm) and high in potassium (0.51 cmol/kg) according to the results of the analysis of the laboratory of Agrocalidad sector in the Tumbaco, province of Pichincha, The babaco presented a satisfactory response to the application of organic manure produced in the area of study, from crop waste and other organic waste profiteers of the place The effects of organic fertilizers contributed to the ground in a dose of 20 tn/has in the case of the humus, organic compost and 10 tn/ha of Fosfoestiercol, compared to the absolute control is described in detail in the results, by analysing the agronomic variables by analysis of variance and comparison of the treatments with the Test Duncan. In various stages of evaluation of the height of the babaco plants fertilized with humus, 6 organic, compost and Fosfoestiercol were similar statistically compared to the absolute control, Except for the corresponding evaluation to the higher plant height with 114.1 cm, which corresponded to the treatment of Compost (20 tn/ha), the same that significantly exceeded the witness, humus, organic and Fosfoestiercol; with regard to the size of sheets, it was determined that organic fertilizers are statistically similar averages with respect to the absolute control, However, the values ranged from 25.9 to 28 cm, corresponding to the extremal values T1 treatments Humus 20tn/ha and T3 Compost 20 tn/ha, the difference between averages did not exceed the ranges of Duncan, but he overcame the treatment of compost for this variable. The number of flowers per plant in the treatments varied within the range of 4.1 to 6.3 flower/plant, extreme values corresponding to the T1 treatments humus and compost to T3 within this interval, the averages do not differ significantly, but the treatment 3 (compost) produced an average of 6.3 flowers per plant, outperforming all other treatments. The values corresponding to the number of leaves per plant was evident that the greater number of leaves per plant was given to the T3 treatment (Compost) 20 tn/ha with an average of 15.9 sheets. The compost gave better results in the number of fruits, so that made the analysis of variance has a value of 21.3 , this us confirms that the babaco has responded significantly compared to the fertilizer of the compost by the production presented. According to tables 12 and 13 of the results, and with the analysis of variance for the size of the fruit in centimeters, the square means or variance of treatments was not significant, which shows us that organic fertilizers contributed to the ground in different phases of the growth of the plant, Did not have a significant effect on this feature agronomic, despite the fact that the larger size of fruit was obtained with the T3 treatment (Compost) averaging 11 cm and the lowest average 10.2 cm that corresponded to the Humus T1 treatment. In the Tables 16 and 17 display the weight of the fruit harvested in seven consecutive collections, in accordance with the fruit reached physiological maturity, the increased performance of 102.47 kg obtained 7 with compost, you only exceeds the Bokashi and this is similar to the treatments Fosfoestiercol humus and absolute control. With these results, we can recommend that the cultivars of babaco should be treated with the compost fertilizer, as an alternative to improve the living standards of producers in different latitudes of the planet, you can also take advantage of the organic materials of the sector itself.